UPAYA PENINGKATAN HASIL BELAJAR MATA PELAJARAN PAI MATERI ASMAUL HUSNA MELALUI METODE CARD SORT KELAS X SMK NEGERI 1 PENUKAL - Reno Apriansyah; Febriyanti Febriyanti; Umtiah Umtiah (GURUKU, 2023)
This study aims to improve the learning outcomes of students in class X PAI by using the card sort learning method. This research was conducted at Penukal 1 State Vocational School, Penukal District, Abab Regency, Lematang Ilir, South Sumatra Province 2022/2023, Odd Semester, namely from September to November 2022, consisting of 20 students. The research method used is the class action research method. This method is carried out in four stages, namely planning, implementing, observing and reflecting. The results of the research conducted show that learning PAI through the application of the card sort learning method can improve PAI learning outcomes. Indicators of success in this study were: completeness of class learning and an increase in the percentage of students who scored a minimum of 75 reaching 100% through the application of the card sort active learning method. Based on the results of the study completeness study in cycle I was 50%, while in cycle II all students had achieved a KKM score of 100%. Based on these results, it can be concluded that learning the card sort method is proven to improve student learning outcomes in class X SMK Negeri 1 Penukal.